2-Bromoethanesulfonate Affects Bacteria in a Trichloroethene-Dechlorinating Culture - Chiu, Pei C. (American Society for Microbiology, 2001)
Long-term exposure to 2-bromoethanesulfonate (BES), an agent known to inhibit methanogenesis, altered the bacterial community structure of an anaerobic enrichment culture that reductively dechlorinated trichloroethene (TCE). BES did not hinder the dechlorination of TCE or other chlorinated ethenes as previously reported, although different intermediates and end products were observed.